Microbial priming for in situ management of paddy straw and its effects on soil microbiological properties under rice-wheat cropping system - KUMAR, AJAY; SINGH, SURENDER; SHIVAY, YASHBIR SINGH; DAS, SHRILA; NAIN, LATA (The Indian Journal of Agricultural Sciences, 2019)
The rice-wheat cropping sequence is the major cropping system of India, which generates large quantities of crop residues. The disposal of paddy straw becomes a major concern in the rice belt of India, as it is burnt to clear the field for succeeding wheat crop. Incorporation of the residues in soil is not feasible because of insufficient time between harvesting of the rice and sowing of wheat, and immobilization of the nitrogen, which causes a reduction in the subsequent crop yield. Microbial interventions to accelerate the degradation may be a viable option for the effective management of farm residues. In this study, a field experiment including three treatments: residues removal (absolute control) and straw retention (@3t/ha) with/without inoculation of fungal consortium was undertaken at the farm of Indian Agricultural Research Institute, New Delhi during 2017-18. Application of fungal consortium (Coprinopsis cineria LA2 and Cyathus stercoreus ITCC 3745) alongwith straw incorporation resulted in a significant increase in the population of microbes. Higher activities of dehydrogenase (8.13 Î¼g TPF /g/d), Carboxymethyl cellulase (0.46 IU/g of soil/d), xylanase (0.06 IU/g of soil/ d), FDA hydrolase (4.31Î¼g fluorescein released /g/h) and alkaline phosphatase (242.98 Î¼g PNP/g/h) enzymes were recorded in the soil of fungal consortium treated plot. Microbial intervention in residue management increased CO2 emission two to three fold within 15-60 days which indicates the role of inoculation in hastening the degradation process. Therefore, microbial priming can be a suitable option for in situ management of paddy straw.